THE INFLUENCE OF BUDGETING PARTICIPATION, BUDGET TARGET CLARITY, ORGANIZATIONAL COMMITMENT ON THE EMPLOYEE’S PERFORMANCE AT BINJAI MUNICIPAL ADMINISTRATION WITH JOB SATISFACTION AS MODERATING VARIABLE - Lesita, Aguinke Br.Hutapea (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to find out and analyze the influence of budgeting participation, budget target clarity, and organizational commitment on the employee’s performance at Binjai Municipal Administration with job satisfaction as moderating variable. The research used causal method. The population was all personnel of Binjai Municipal Administration, and the samples were taken by using Slovin formula. It also used judgment samples consisted of Budget Users, Financial Administrative Officials, and Technical Activity Administrator in 33 SKPD (Regional Work Unit) of Binjai Municipal Administration. The data were gathered by distributing questionnaires and analyzed by using multiple linear regression analysis and residual test with an SPSS software program. The result of the research showed that, simultaneously and partially, budgeting participation, budget target clarity, and organizational commitment had significant influence on the employees’ performance at Binjai Municipal Administration. Job satisfaction as moderating variable could moderate the correlation of budgeting participation, budget target clarity, and organizational commitment with the employees’ performance at Binjai Municipal Administration.